Design and test of a dual-axis layered rotary tillage stubble exterminator in saline-alkali land based on discrete elements - Zhao, Zhuang; Wang, Dongwei; Shang, Shuqi; Guo, Peng; Gao, Zenghui; Xia, Chao; Yan, Haipeng; Hou, Jialin (International Journal of Agricultural and Biological Engineering, 2024)
Considering the problems of poor straw mulching performance, low soil crushing rate and poor straw mulching performance of the traditional rotary tiller on saline-alkali soils, a two-axis layered rotary stubble cutter for saline-alkali soils with front-axis positive rotation of the front axle and rear-axis counter-rotation of the rear axle was developed, focusing on the kinetic properties of the straw and soil under positive and counter-rotation. In addition, the most important structural parameters and the arrangement of the front-axis stubble cutting knife and the rear-axis return knife were analyzed and determined. Hertz-Mindlin with bonding was used to create a discrete element model of the agglomerate of implement, straw and soil. The forward speed, horizontal distance and vertical distance were used as test factors, and the straw return rate and soil fragmentation rate were used as test indexes to analyze the straw-soil transport law under different operating parameters from a microscopic point of view, and then Design-Expert was used to conduct the test 1.07 km/h, horizontal distance of 569.55 mm, vertical distance of 176.59 mm. To validate the performance of the two-axis, layered rotary tiller, a field trial was conducted and the results show that the straw return ratio was (91.59±0.41)%, soil fragmentation ratio was (91.90±0.29)% and tillage depth stability was (91.52±0.46)%, which met the requirements for peanut seedbed preparation on saline-alkali land. Keywords: saline-alkali land, straw return, soil fragmentation, dual-axis layering, discrete element simulation, field trial DOI: 10.25165/j.ijabe.20241705.8950 Citation: Zhao Z, Wang D W, Shang S Q, Guo P, Gao Z H, Xia C, et al. Design and test of a dual-axis layered rotary tillage stubble exterminator in saline-alkali land based on discrete elements. Int J Agric & Biol Eng, 2024; 17(5): 163-175.